2017
DOI: 10.1175/jcli-d-16-0033.1
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Eurasian Snow Cover and Indian Summer Monsoon Rainfall: Importance of the Delayed Hydrological Effect

Abstract: This observationally based study demonstrates the importance of the delayed hydrological response of snow cover and snowmelt over the Eurasian region and Tibet for variability of Indian summer monsoon rainfall during the first two months after onset. Using snow cover fraction and snow water equivalent data during 1967–2003, it is demonstrated that, although the snow-albedo effect is prevalent over western Eurasia, the delayed hydrological effect is strong and persistent over the eastern part. Long soil moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 79 publications
0
48
0
Order By: Relevance
“…As noted previously (Dirmeyer & Halder, ; Roundy et al, ), this causes a wet surface bias over agricultural areas, especially noticeable over the midwestern United States, with excessive ET, very shallow boundary layers, and erroneously weak land‐atmosphere coupling (Dirmeyer et al, ). Furthermore, snowpack and snowmelt biases in this model have some effect in April and May at high latitudes (Halder & Dirmeyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously (Dirmeyer & Halder, ; Roundy et al, ), this causes a wet surface bias over agricultural areas, especially noticeable over the midwestern United States, with excessive ET, very shallow boundary layers, and erroneously weak land‐atmosphere coupling (Dirmeyer et al, ). Furthermore, snowpack and snowmelt biases in this model have some effect in April and May at high latitudes (Halder & Dirmeyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…More snow over western Eurasia and less snow over eastern Eurasia were unfavourable for Indian summer monsoon (ISM) (e.g., Kripalani and Kulkarni, ; Dash et al ., ; Singh and Oh, ) while being favourable for EASM (e.g., Kripalani et al ., ; Yim et al ., ; Wu et al ., ). Halder and Dirmeyer () proposed that winter and spring Eurasian snow cover and snow melt have a delayed hydrological effect on the ensuing ISM. Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…More snow over western Eurasia and less snow over eastern Eurasia were unfavourable for Indian summer monsoon (ISM) (e.g., Kripalani and Kulkarni, 1999;Dash et al, 2005;Singh and Oh, 2005) while being favourable for EASM (e.g., Kripalani et al, 2002;Yim et al, 2010;Wu et al, 2014). Halder and Dirmeyer (2017) proposed that winter and spring Eurasian snow cover and snow melt have a delayed hydrological effect on the ensuing ISM. Zhang et al (2017) showed through observations and numerical experiments that the west-east dipole structure of Eurasian snow may significantly affect EASM (especially over China) through anomalous mid-latitude Eurasian wave propagation.…”
mentioning
confidence: 96%
“…Eurasian snow is one of the major land surface processes, which also has an inverse relationship with the ISMR (Hahn and Shukla, 1976;Vernekar et al, 1995;Kripalani and Kulkarni, 1999;Fasullo, 2004;Singh and Oh, 2005;Halder and Dirmeyer, 2017). The pioneering study by Blanford (1884) explained the negative correlation between winter snow over the Himalaya and subsequent summer monsoon rainfall over India.…”
Section: Introductionmentioning
confidence: 99%